Digital agriculture and world food security - Yining Cheng (Informaciâ i Innovacii)
Food security is a global problem, especially in the context of the current epidemic that is raging in the world. As the number of people infected with the new coronavirus reaches 10 million worldwide, a global food crisis is inevitable. The key to solving the problem of food security is to ensure the safety of production of a growing number of agricultural products, ensuring the safety of transportation and storage. In the context of rapid development of the digital economy, it is necessary to combine agriculture with digitalization, create an information database on agriculture, use digital methods, including for effective prevention of natural disaster risks, minimize losses, reduce production costs, and so on. Food aid cannot fundamentally solve the problem of food security, especially in those countries where the level of agricultural development remains low: these countries and regions need digital agriculture to counter risks and provide food for their populations. This is the only way we can achieve precise (coordinate) farming, create “smart” agriculture, and achieve the goal of zero hunger in the shortest possible time.